Group portrait of YWCA hikers - Unknown:::Creator::::::::::::
Photograph shows a group of teenage girls and one woman hiking down the upper road. They were learning how to take snapshots. They have a box with the Wesson Oil logo on it and below the logo are the words "[No] Drip Bottle." The girl in the first row on the far right is holding a baseball bat and the girl on the far left is leaning on a jug with a swinging a handle.